African Indigenous Oral Traditional Endarkened Feminist Practice: Indigenous knowledge on the wrong side of Matter - Jude, Julia (Murmurations: Journal of Transformative Systemic Practice, 2017)
Systemic and social constructionist practitioners demand that issues of social justice are paid attention to in all aspects of practice through the application of multi-perspectives. But multi-perspectives may not be so multiple as they are often embedded in ideas and theories that stem from Western European frames. This paper examines the place material presence (objects) have within the discourse of African Indigenous Oral Traditional Endarkened and Feminist Practice (AIOTEFP). An example of the application of AIOTEFP is offered as a way of demonstrating inventive ways that AIOTEFP can be practiced, offering alternative accounts that privilege marginalised voices. I argue that if social justice, is to be achieved, responsible communication and attentiveness to the needs of others, have to be an important part of this process, to create discourses that go beyond a Western European frame of knowledge.